Biphenyl appended BODIPY derivatives showing combined environmental polarity and heavy metal cation sensing functionality1. (27th August 2015) - Richards, Gary James; Gobo, Yuki; Yamamura, Masaki; Nabeshima, Tatsuya
<x xml:space="preserve">Abstract</x> Novel BODIPY derivatives exhibiting environmental polarity and combined environmental polarity/Hg2+ and Pb2+ fluorescence sensing properties have been prepared. The sensing properties are the result of a switchable photoinduced electron transfer (PeT) quenching mechanism.